Political and Economic Inequality: Insights from Philippine Data on Political Dynasties - Mendoza, Ronald U (Archīum Ateneo, 2021)
There is an extensive empirical literature on economic inequality; yet few studies examine its political underpinnings. This article contributes to the nascent literature in this area by developing and analyzing a new measure of political inequality. Drawing on a comprehensive provincial-level dataset on local government leadership in the Philippines; this article develops a political inequality index based on the concentration of elective positions among political dynasties. It then empirically examines the possible links among economic inequality; political inequality; and development outcomes across Philippine provinces. This study finds that economic inequality displays a nonlinear relationship with indicators of human development—there is a positive correlation at lower levels of human development; and a negative correlation at higher levels. On the other hand; unlikeeconomic inequality; political inequality seems to be associated with weaker development outcomes; regardless of the level of development the province is in. This finding emphasizes how future research on political inequality could yield new insights into the persistence and depth of poverty; human development; and other forms of social and economic inequality.